Moral Hazard or Pent-up Demand? Evidence from a Quasi-experiment Concerning the Introduction of Universal Health Coverage in Four Provinces of Thailand - Pongtipan, Panyapon (Journal of Applied Economics and Management Strategy, 2024)
Historically relatively few Thai people were covered by health insurance, and most medical treatment was inaccessible or expensive. The implementation of Universal Health Coverage (UHC) since 2001 has entitled everyone to affordable treatment. It was speculated that this would result in excess healthcare consumption – a moral hazard. The current study was designed to determine whether moral hazard existed here, and if so, its magnitude. The study used panel data relating to 1,129 individuals’ socioeconomic circumstances and utilization of healthcare services from 2000 to 2006 in four Thai provinces (Buriram, Chachoengsao, Lopburi and Sisaket). It compared the healthcare utilization of individuals before and after the implementation of UHC. Analysis was performed using a novel estimator, a nonlinear in Extended Two-Way Fixed Effect Difference in Differences (ETWFE DID), which was applied to individual panel data to investigate changes in individual behaviors before and after the introduction of UHC. The analysis provides evidence of a temporary 2.14% increase in outpatient utilization in previously uninsured individuals immediately following the introduction of UHC. The increase may be attributed to pent-up demand or “novelty factor”. There is no evidence of sustained moral hazard.